Identification of the metallurgical parameters explaining the corrosion susceptibility in a 2050 aluminium alloy. (January 2016) - Guérin, Mathilde; Alexis, Joël; Andrieu, Eric; Laffont, Lydia; Lefebvre, Williams; Odemer, Grégory; Blanc, Christine
Highlights: Intergranular corrosion occurs in AA 2050 without T1 phase at the grain boundaries. Interfaces with a low level of misorientation have a higher corrosion resistance. Corrosion mechanisms are also linked to the internal misorientation of the grains. Galvanic coupling at the polycrystal scale was assumed. Grains oriented in the (1 1 1) planes were the most susceptible to corrosion. Abstract: The corrosion behaviour of a 2050 aluminium alloy was studied in a NaCl solution. The structure of precipitation did not fully explain the susceptibility to intergranular (in the -T34 state) and intragranular corrosion for the aged state (the -T8 state). A relationship between the nature of interfaces, the grains characteristics (size, internal misorientation and orientation according to the plane exposed to the electrolyte) on one hand and the corrosion susceptibility of the alloy on the other hand was clearly established. Galvanic coupling between grains with different internal misorientations helped to explain the intergranular corrosion susceptibility of the -T34 state.